The Influence of TLR4, CD14, OPG, and RANKL Polymorphisms in Periodontitis: A Case-Control Study - Joana Maira Valentini Zacarias; Josiane Bazzo de Alencar; Patrícia Yumeko Tsuneto; Victor Hugo de Souza; Cléverson O. Silva; Jeane Eliete Laguila Visentainer; Ana Maria Sell (Mediators of Inflammation)
The pathogenesis of periodontitis involves a complex interaction between the microbial challenge and the host immune response. The individual immunoinflammatory response has a great contribution in the pathogenesis of the disease and becomes a trigger in the process of bone remodeling which is a characteristic of the disease. Thus, the aim of this study was to evaluate the influence of the TLR4 A896G (rs4986790), TLR4 C1196T (rs4986791), CD14 C-260T (rs2569190), RANKL (TNFSF11, rs2277438), and OPG (TNFSF11B C163T, rs3102735) polymorphisms in periodontitis. A case-control study was conducted on patients with periodontitis (N=203) and controls (N=213) over 30 years of age, without diabetes mellitus, acute infections, and osteoarthritis, and patients without aggressive periodontitis, i.e., stage IV and C degree of periodontitis, and any periodontal treatment performed in the last 6 months. Genotypes were determined by the PCR-RFLP and sequencing method. The frequency comparisons between case and controls were performed using the chi-square test and logistic regression (OpenEpi and SNPStats software). The risk (OR) was evaluated for values of P<0.05. Differences in TLR4, CD14, RANKL, and OPG genotype and allele frequency distributions were not observed between patients and controls. However, some variants were a risk factor for the development of periodontitis when considering gender and smoking habits. The TLR4 896 A/G genotype was a risk factor for periodontitis in males (OR=2.86), and the TLR4 1196C/C genotype was a risk factor for nonsmoking males (OR=1.85) when compared to women. The RANKL A/A and the OPG T/C genotype was associated with the risk of the disease in nonsmoking men compared to nonsmoking women with the same genotype (OR=1.96 and OR=2.9, respectively). In conclusion, TLR4, CD14, RANKL, and OPG variants were not associated with periodontitis. However, TLR4, RANKL, and OPG polymorphisms could be a risk for periodontitis in males regardless of smoking habits.